ARIMA Model for Gold Bullion Coin Selling Prices Forecasting - Lazim Abdullah (International Journal of Advances in Applied Sciences, 2012)
Time series forecasting is an active research area that has drawn considerable attention for applications in a variety of areas. Auto-Regressive Integrated Moving Average (ARIMA) models are one of the most important time series models used in financial market forecasting over the past three decades but not very often used to forecast gold prices.  This paper attempts to address the forecasting of gold bullion coin selling prices. The forecasting models ARIMAs are applied to forecast the gold bullion coin prices. The result suggests that ARIMA (2, 1, 2) is the most suitable model to be used for forecasting gold bullion coin prices. Closer examination suggests that the gold bullion coin selling prices are in upward trends and could be considered as a worthy investment.